Penerapan Nilai-Nilai Moderasi Beragama Berdasarkan Al-Qur’an Dan Hadist Di MAN 2 Pesisir Selatan - Zulfira Zulfira (Khazanah : Journal of Islamic Studies, 2023)
This research aims to analyze the implementation of religious moderation values in the subjects of Islamic Education and Character at MAN 2 Pesisir Selatan based on the Qur'an and Hadith. This study uses a qualitative descriptive method. Primary data was obtained from Islamic Education and Character teachers through interviews and observations, while secondary data was collected through documentation from student and teacher books, lesson plans, and syllabi of Islamic Education and Character subjects under the Merdeka Belajar Curriculum. The research findings indicate that the application of religious moderation values by teachers in the subjects of Islamic Education and Character is done through the use of an additive approach and the development of indicators for achieving the Basic Competencies stated in the lesson plans and syllabi, taking into account the principles of relevance, consistency, and sufficiency. The study also found that the implementation of religious moderation values is carried out through the exemplary behavior of teachers in the school and the community.